THE SCHOOL PROMOTING A CIVILIZING PROCESS IN THE DEAF STUDENT INCLUSION IN THE PHYSICAL EDUCATION CLASSES (Fiep Bulletin - online, 2017)
The present article searched analyze the current legislation that broach about inclusion, specially the deaf peopleinclusion. To the deaf community talking about school age the best methodological arrangement is being in deaf schools duringthe main turn and the inclusive in the extracurricular activities. The obligatory curriculum of all schools have the Physical Education subject that contributes as a socialization and student's biopsychomotor development instrument. This article purposeis debate the inclusion importance to mediate this discussions and the society's view that, well directed, helps the deafcommunity in the diverse groups and social institutions insertion. The methodology used was the basic nature and exploratoryresearch. It is conclude the developed society, in the middle of the third Millennium, discuss the deaf inclusion and sports practicetheme, but little effective actions made the physic education practice possible to this community. To let this lawsuit happen, it istotal relevance and interest of all society the investment in the teacher formation in a continuous form to the teacher' possibility toobserve their students and their praxis, and overwork in a creative and appropriated form, because they are responsible bypreparing their students to the modernity challenges.